AI-Integrated Classroom Action Research for Enhancing Students' Critical Thinking Skills: A Systematic Review - Yusriani Yusriani; Andi Yuyung (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The rapid development of Artificial Intelligence (AI) in education has opened new opportunities for pedagogical innovation, including in the practice of Classroom Action Research (CAR). This study aims to analyze and synthesize how AI is integrated across the CAR cycle and to examine its contribution to the development of students' critical thinking skills. A systematic literature review was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. Twenty peer-reviewed articles published between 2023 and 2026, retrieved from Google Scholar, ScienceDirect, and ERIC, were analyzed through thematic categorization and narrative synthesis. AI is no longer positioned merely as an instructional tool; it is increasingly embedded across all stages of the CAR cycle, with the most prominent role emerging in the observation and reflection phases, where it supports learning data analysis and delivers rapid, adaptive feedback. AI integration is associated with improved student engagement and learning outcomes, as well as stronger analytical, evaluative, and argumentation skills. However, the benefits are not automatic: unstructured or excessive use of AI risks fostering dependency and reducing the depth of students' independent thinking. This review offers one of the first comprehensive syntheses of AI integration across the entire CAR cycle—planning, acting, observing, and reflecting—linking it explicitly to critical-thinking development within a reflective, teacher-led inquiry framework, an intersection that remains underexplored in the extant literature.